Pathogenicity of bacterium carried by Bursaphelenchus mucronatus on Pinus yunnanensis - Li Shujiang; Zhu Tianhui; Zhang Xinghua (浙江大学学报. 农业与生命科学版)
Pine wood nematode (PWN) is a destructive disease to pines. For the research on its pathogenic mechanism, the theory which is about the complex infection of PWN and the bacterium carried by it is recognized. Bursaphelenchus mucronatus is considered as a related species of Bursaphelenchus xylophilus, which may be differentiation with the homologous species in different environments. In early studies, B. mucronatus was served as contrast species to B. xylophilus due to the weak or lacking pathogenicity. But recently, many reports have pointed out that it has the strong pathogenicity and can cause the widespread death of pines, which referred to Pinus thunbergii, P. yunnanensis, P. taiwanensis, P. densata, etc. The large numbers of P. yunnanensis were dead in Sichuan in recent years. However, no systematic study was conducted on the pathogenicity of the bacterium carried by B. mucronatus. This study has the aim of evaluating the effects of the bacterium carried by B. mucronatus on wilting ratio and phenylpropanoid metabolism of pine needles, and further exploring the effect of bacterium in the pathogenic process of B. mucronatus.Two-year-old P. yunnanensis seedlings, B. mucronatus isolated from PWN disease district in Sichuan, the bacterium carried by B. mucronatus and its metabolite as the materials, the wilting ratio was calculated, and the total phenol content, phenylalanine ammonia-lyase (PAL), polyphenol oxidase (PPO), peroxidase (POD) activities were determined by the inoculation of burette to branch phloem of P. yunnanensis in laboratory, which represented the pathogenicity of the bacterium and its metabolite on P. yunnanensis.The results showed that Pectobacterium cypripedii and its non-protein metabolite had strongest effect on P. yunnanensis in 26 species of bacteria isolated from the surface of nematodes, and the wilting degree and wilting ratio were significantly high in these two treatments. They caused the accumulation of total phenol content and the changes of PAL, PPO and POD activities, the PPO and POD activities of which increased from 12 h to 24 h and declined after 24 h, and PAL activities declined during 12 48 h. Moreover, in above each index, significant correlation with wilting ratio was observed, but among the indexes in phenylpropanoid metabolism, only PAL and PPO activities were found to have a significant correlation.It is concluded that P. cypripedii and its non-protein metabolite can continuously decrease the phenolic antioxidants, which makes the metabolism to be disordered and induce cell toxicity of the needles through affecting the phenylpropanoid metabolism. And then, the needles display lesion, fading, browning, drying and even death. The above results reveal that the occurrence and development of PWN disease is closely related to the abnormal changes of the phenylpropanoid metabolism in host.